VI - occurence of domatia in species and hybrids of Vitaceae familiae - Barros, Myrthes A. Adamoli de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
This paper deals with the ocurrence of domatia in hybrids of Vitaceae family. With this paper we finish a serie of works in according to a plan programmed about this subject. The author found domatia in 47 of 120 hybrids studied. The domatia found were of the types: "en touffe de poils" and "in pochette", according to CHEVALIER & CHESNAIS (1941). The leaves were examinated in both sides and in the junction of the blade with the petiole. This paper is the 6 th and last work about this subject.